2013
DOI: 10.1016/j.tim.2012.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bacterial interactions on pneumococcal colonization of the nasopharynx

Abstract: Streptococcus pneumoniae (the pneumococcus) is a common commensal inhabitant of the nasopharynx and a frequent etiologic agent in serious diseases such as pneumonia, otitis media, bacteremia, and meningitis. Multiple pneumococcal strains can colonize the nasopharynx, which is also home to many other bacterial species. Intraspecies and interspecies interactions influence pneumococcal carriage in important ways. Co-colonization by two or more pneumococcal strains has implications for vaccine serotype replacement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
139
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(145 citation statements)
references
References 103 publications
(130 reference statements)
2
139
0
Order By: Relevance
“…One might speculate that the decrease in diversity is caused by the outgrowth of pathogens, which predisposes to invasive infection, but this hypothesis can be tested only in a longitudinal study. Our initial working hypothesis was that commensal bacteria keep the facultative pathogens colonizing the nasopharynx in check (21). This could prevent their descent into the lungs and invasive infection.…”
Section: Discussionmentioning
confidence: 99%
“…One might speculate that the decrease in diversity is caused by the outgrowth of pathogens, which predisposes to invasive infection, but this hypothesis can be tested only in a longitudinal study. Our initial working hypothesis was that commensal bacteria keep the facultative pathogens colonizing the nasopharynx in check (21). This could prevent their descent into the lungs and invasive infection.…”
Section: Discussionmentioning
confidence: 99%
“…Mitis group streptococci are early colonizers of oral cavity surfaces and form the basis of many of the polymicrobial communities found in the mouth and nasopharynx (Aas et al, 2005;Kanasi et al, 2010;Shak et al, 2013;Xu et al, 2014a). Such communities may also contain C. albicans, which is carried by~40 % of the healthy adult population (Clayton & Noble, 1966), and it is suggested that synergistic interactions between C. albicans and streptococci can promote carriage as well as disease (Dutton et al, 2014;Falsetta et al, 2014;Xu et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…Since vaccine-type strains were those found to be correlated with S. aureus carriage, this raised much concern that the introduction of the vaccine would indirectly cause a rise in S. aureus carriage and infection. 7,11,14,15 The idea that external interventions in ecosystems could damage the natural equilibrium by eliminating a less virulent 'predator' and result in undesirable emergence of a possibly more virulent 'prey' is not new and was shown decades ago for pests and pesticides. 74 The clinical trial that first suggested interference between S. pneumoniae and S. aureus found a rise in S. aureus otitis media cases following vaccination with PCV7 compared to a non-vaccinated group.…”
Section: Clinical Implications Of the Pcv Effect On Thementioning
confidence: 99%
“…This finding, together with an earlier clinical trial that reported increased S. aureus otitis media following PCV vaccination, 13 raised much concern 3,7,14,15 ; if S. pneumoniae carriage protects from S. aureus carriage and the introduction of the pneumococcal conjugate vaccines (PCV) results in decreased S. pneumoniae carriage, this could potentially lead to an increase in S. aureus carriage, and infection. In this review, we summarize the various suggested mechanisms of this inverse correlation, and the clinical implications reported following PCV introduction to date in various geographical regions.…”
Section: Introductionmentioning
confidence: 99%